PENGARUH GAME ONLINE FREE FIRE TERHADAP MINAT BELAJAR PADA ANAK USIA SEKOLAH DASAR DI LINK.KEDUNG BULUS - Anita Nurbayanti; Popi Dayurni; ISMATULLAH (STKIP Subang, 2026)
This study aims to determine whether there is an influence of free fire online games on interest in learning. This research is a quantitative study with a correlational method. Data collection techniques using questionnaire distribution and data analysis were carried out with prerequisite tests (normality test and linearity test) and hypothesis testing (simple linear regression test). The results obtained using the t-test showed a significant negative influence between playing Free Fire games and students' interest in learning. The calculated t value (-3.550) > t table (1.714) with a significance level of 0.002. This means that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. This means that the more often students play the Free Fire game, the more their interest in learning tends to decrease. Research has revealed that time spent playing Free Fire games has a significant influence on children's interest in learning. Therefore, it is very important for parents to play an active role in managing children's playing time so as not to interfere with their learning process and cognitive development.